Statistical correlations between extractable Ca, Mg, K and P from fresh and laboratory prepared soil samples - Moshia, Matshwene Edwin (My University, 2005)
Drying, grinding and sieving are commonly employed to facilitate the handling, storage of soil samples on which chemical, biological, and physical analyses are to be performed. These laboratory protocols have the potential to alter soil chemical characteristics and may result in unrealistic estimates of in situ chemical processes. The effect of laboratory soil sample preparation on level of extractable Ca, Mg, K, and P was determined. The analyses were done on laboratory prepared soil samples and compared with the characteristics of fresh soil samples (field-moist) for the same soils that were sampled in pairs of 20 per location of the four locations. Samples were collected at Tshiombho irrigation scheme, Dal water farm, Magoebaskloef pine tree farm and Syferkuil experimental farm. The results indicated that soil samples should be kept at their field moist status until experimental procedures are done. Concentration of most extractable ions for the two preparation methods correlated closely. However, grinding and air-drying increased P concentration by 1.3 to 1.55 times, and decreased the concentration of K by 2 to 2.5 times and this is caused by soil moisture depletion. According to the results, there should be different preparation methods for different extractable ions, Ca and Mg can be continued analysed on laboratory prepared soil samples but soil pH, K and P should be analysed on fresh soil samples. If such is not done, then the effects should be considered when interpreting the results for fertilizer recommendations.
Thesis (Ph.D. (Agriculture)) --University of Limpopo (Turfloop Campus), 2005
Keywords: Laboratory prepared soil samples; Fresh soil samples; Soils -- Analysis; Soils -- Composition